Consuming in response to loneliness: Bright side and dark side effects. (August 2022) - Fumagalli, Elena; Shrum, L.J.; Lowrey, Tina M.
Abstract: This review synthesizes the most recent advances in psychology investigating the link between loneliness and consumption. We structure the review around the motives that loneliness activates, based on the Evolutionary Theory of Loneliness. More specifically, we detail how consumers use consumption experiences to repair perceived deficiencies in their belongingness needs, and how the motive to improve social connections through consumption can have both positive (bright side) and negative (dark side) effects. We also discuss how loneliness can activate a self-preservation motive that can breed interpersonal mistrust and thus potentially impede reconnection. We conclude by reviewing research on the depleting effects of loneliness on self-regulatory resources and the dark side effects of this depletion on self-control.